The Influence of Diabetic Peripheral Neuropathy on the Duration of Sciatic Nerve Block with 1.3% Liposomal Bupivacaine and 0.25% Bupivacaine Hydrochloride in a Mouse Model - Liljana Markova; Erika Cvetko; Chiedozie Kenneth Ugwoke; Simon Horvat; Nejc Umek; Tatjana Stopar Pintarič (MDPI AG, 2022)
Little is known regarding the pharmacological properties of extended-release local anesthetics in the setting of diabetic peripheral neuropathy. We investigated and compared the duration of sciatic nerve block following administration of clinically relevant concentrations of liposomal bupivacaine (LB) and bupivacaine hydrochloride (BH) in diabetic mice with peripheral neuropathy. In this prospective, randomized, and double-blind study, twenty-four female C57BL/6J-OlaHsd mice were assigned to a streptozotocin-induced type 1 diabetes group and a control group without diabetes. The presence of peripheral neuropathy was established by assessing the duration of thermal latency of the plantar and tail-flick tests, following which both groups were subdivided into two subgroups in which 35 mg/kg of 1.31% LB and 7 mg/kg of 0.25% BH were respectively administered for sciatic nerve block. The average sensory block duration with BH was 106 min and 117.1 min in the control and diabetic groups, respectively. With LB, the average sensory block duration was 118 min in the control mice, while in mice with diabetic peripheral neuropathy, the average block duration was significantly longer and above the 270 min limit set in our study. Accordingly, sensory block duration was longer with LB compared to BH, and diabetic peripheral neuropathy significantly increased sciatic nerve block duration with LB.